Research Progress of the Role of Anthocyanins on Bone Regeneration - Mao, Wei; Huang, Guowei; Chen, Huan; Xu, Liangliang; Qin, Shengnan; Li, Aiguo (Frontiers in Pharmacology, 2021)
Bone regeneration in osteoporosis and fragility fractures which are highly associated with age remains a great challenge in the orthopedic field, even though the bone is subjected to a continuous process of remodeling which persists throughout lifelong. Regulation of osteoblast and osteoclast differentiation is recognized as effective therapeutic targets to accelerate bone regeneration in osteopenic conditions. Anthocyanins (ACNs), a class of naturally occurring compounds obtained from colored plants, have received increasing attention recently because of their well-documented biological effects, such as antioxidant, anti-inflammation, and anti-apoptosis in chronic diseases, like osteoporosis. Here, we summarized the detailed research progress on ACNs on bone regeneration and their molecular mechanisms on promoting osteoblast differentiation as well as inhibiting osteoclast formation and differentiation to explore their promising therapeutic application in repressing bone loss and helping fragility fracture healing. Better understanding the role and mechanisms of ACNs on bone regeneration is helpful for the prevention or treatment of osteoporosis and also for the exploration of new bone regenerative medicine.